DEVELOPING WEB-BASED INFORMATION SYSTEM FOR BOOKING INFLUENCER SERVICES ON CYCLONE MANAGEMENT - Frisca Fitria; Genta Sahuri (President University, 2022)
Cyclone Management is an influencermarketing agency based in Cikarang, Indonesia. CycloneManagement's talent portfolio includes 80+ portfoliosand hundreds of tags from talents who have alreadycollaborated with several big brands on its InstagramFeeds. This final project will discuss establishing a web-based information system for booking influencer servicesin cyclone management. This system will displayinformation about talent to help brands choose the rightinfluencer to promote their products.